A Systems study on Solid Waste Collection - Dacoco, Bernadette R.; Dag, Benito C.; dela Cruz, Elenita A.; Jaspe, Nilo B.; Panga, Mario Bernardo S.; Plata, Melinda C. (College of Engineering, 1990)
The System of Interest is the Refuse Collection System of the Metro Manila Solid Waste Management. The objective of the study is to orient and put to practical use the knowledge of system analysis and design in the collection of solid waste. Further attempts are included in the implementation through guidelines presented by Gantt chart with dates of possible stage of completion. The project team documented the system under study by studying the solid waste management of Metro Manila. Definition of solid waste and adverse effect of mismanagement are studied. The six identifiable functional elements of solid waste management are waste generation, storage, collection, transfer and transport, processing and recovery, and disposal. Measures of performance are determined to be the basis for analysis and design. The present system is also studied by its major components namely: manpower, equipment, systems and procedures, information subsystem, and budget appropriation and actual expenditures. The analysis embarks on the identification of system variables, parameters, and constraints and finally analyses and evaluates the present system. Some problem areas are enumerated with corresponding cause and effect diagrams are presented. The problem areas include collection inefficiency, lack of worker's protection, low social acceptance, high cost of solid waste per ton per day, and inflexibility to seasonal variation. Productivity and efficiency measures were computed to compare the performance of the different areas under North Sector. They were analyzed with respect to standard values obtained from previous studies on the subject. Per capita budget allocation was also computed to find out the correlation of budget allocation to system efficiency. Quezon City registered the highest efficiency rating, 92.3%, higher than the 90% standard. Valenzuela has the lowest efficiency with 51.45%. Per capita budget allocation computations reveal that Quezon City registered the lowest per capita cost while Valenzuela registered the highest cost. Indeed, the results were just as expected that budget allocation is directly proportional to efficiency. Alternative system designs were generated by considering different possible combinations of system alterable. Routing and Scheduling were designed based on area type and relative distances from the dumpsite to ESC office, from area office to collection route, and from the collection area to the dumpsite. There are sixteen alternative designs which are combinations of different schedules and equipment options. Consideration was also made for choice of either contractual or owned options. The design of the collection MIS is based on the information requirements for effective decision making. Unlike the present monitoring system, the new information system now includes data for the calculation of productivity indices pertaining to collection and transport. Choice of the alternative combination of equipment and scheduling is based on the alternative that yields the least present worth cost. The selection phase showed that the schedule of daily two shifts for markets and main thoroughfares and thrice a week collection for other areas is the least present worth cost alternative. We will have to buy 16 (7-cu.m.) trucks for the chosen alternative. System implementation will ensure the gradual transition from the old system to the new system. Total implementation time is five months which is divided into five stages: 1) pre-integration period; 2) integration period; 3) operationalization period; 4) post-implementation evaluation period; 5) redesign period.